Application of Theory of Planned Behavior to counterfeit garment brands purchase: a qualitative research - Dhingra, Dr. Ambika Bhatia, Taranpreet Kaur (International Journal of Scientific Research and Management (IJSRM), 2014)
Theory of Planned Behavior has been used in a number of studies to understand the consumerbehavior. Almost all such researches have utilized quantitative methods for research. In this research, anattempt has been made to apply the Theory of Planned Behavior to the counterfeit garment brand purchaseusing qualitative methods. This research tried to identify the factors that influence consumers to buy or notto buy counterfeit garment brands based on the constructs of Theory of Planned Behavior. Three focusgroup interviews were conducted for 30 people in a group of ten each. The three groups comprised ofrespondents from different age groups. The responses were hence analyzed to identify the similarities anddifferences in the factors of importance while purchasing branded/ counterfeit garments between the threegroups of respondents